2020
DOI: 10.3390/pharmaceutics12030221
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activity of Ionic Liquids and Organic Salts Based on Penicillin G and Amoxicillin hydrolysate Derivatives against Resistant Bacteria

Abstract: The preparation and characterization of ionic liquids and organic salts (OSILs) that contain anionic penicillin G [secoPen] and amoxicillin [seco-Amx] hydrolysate derivatives and their in vitro antibacterial activity against sensitive and resistant Escherichia coli and Staphylococcus aureus strains is reported. Eleven hydrolyzed β-lactam-OSILs were obtained after precipitation in moderate-to-high yields via the neutralization of the basic ammonia buffer of antibiotics with different cation hydroxide salts. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 96 publications
1
44
0
Order By: Relevance
“…The cation hydroxides are prepared immediately before their addition from the corresponding halide salts by anion exchange from a hydroxide resin such as Amberlyst IRA-400 (OH). Whenever this methodology is performed with zwitterionic APIs [19,22] such as fluoroquinolones, it is required that the reaction proceeds in ammonia buffer solution so that complete ionisation can occur. The pure API-OSILs were isolated in very high yields (93-100%) after recrystallisation from chloroform/methanol mixtures.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The cation hydroxides are prepared immediately before their addition from the corresponding halide salts by anion exchange from a hydroxide resin such as Amberlyst IRA-400 (OH). Whenever this methodology is performed with zwitterionic APIs [19,22] such as fluoroquinolones, it is required that the reaction proceeds in ammonia buffer solution so that complete ionisation can occur. The pure API-OSILs were isolated in very high yields (93-100%) after recrystallisation from chloroform/methanol mixtures.…”
Section: Synthesismentioning
confidence: 99%
“…For more than a decade, active pharmaceutical ingredients as organic salts and ionic liquids (API-OSILs) have risen in academia as an alternative formulation for low bioavailable drugs [9][10][11][12]. This third generation of ionic liquids [9] consists on the combination of APIs as cations or anions with organic counterions, thereby inducing distinctive physicochemical properties over the original drugs and reduced toxicity to healthy cells, thus rendering a potentially enhanced pharmaceutical activity in comparison to the API [13][14][15][16][17][18][19][20][21][22][23][24][25]. Our works involving the preparation of API-OSILs from, e.g., β-lactam (ampicillin [18][19][20][21], penicillin [22] and amoxicillin [22]) and fluoroquinolone [18,23] antibiotics, NSAIDs (ibuprofen [17,18], naproxen [18]), bone antiresorptive agents (zoledronic [24] and alendronic [25] acids), among others, have shown that the combination of an API, either as a cation or as an anion, with suitable biocompatible counter-ions can increase the water solubility of the parent drug and even change its biological effect [10,17,[23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The selection of protonated organic superbases (1,1,3,3-tetramethylguanidinium [TMGH] and 1,5-diazabicyclo(4.3.0)non-5-enium [DBNH]) and quaternary ammonium (cholinium [Ch] and 1-(2-hydroxyethyl)-3-methyl-1H-imidazol-3-ium [C 2 OHMIM]) cations relied on the known information about their biocompatibility [15,23]. Despite their low toxicity, the combination of these cations with other APIs has rendered highly active API-OSILs in the past, in particular antimicrobial and anti-tumoral [19,20,22]. The preparation of compounds 1-4 consisted of the addition of the diluted superbases to a dispersion of ALN (pathway A).…”
Section: Synthesis and Characterization Of Aln-osilsmentioning
confidence: 99%
“…Ionic Liquids (ILs) are defined as salts with a melting point below 100 • C, which display peculiar properties such as negligible vapor pressure, high thermal and chemical stability and tunable physicochemical properties according to the cation-anion combinations. These novel API-OSILs can improve the drug performance in terms of stability, solubility, permeability, biological activity and delivery [10][11][12][13][14][15][16][17][18][19][20][21][22]. Recent achievements showed that the suitable combination between different families of pharmaceutical drugs such as NSAIDs (e.g., ibuprofen and naproxen [15,16]), β-lactam (e.g., ampicillin, amoxicillin, penicillin [16][17][18][19][20]) and fluoroquinolone (ciprofloxacin, norfloxacin [16,21]) antibiotics and bone antiresorptive agents (zoledronic acid [22]) rendered novel pharmaceutical drug formulations based on OSILs.…”
Section: Introductionmentioning
confidence: 99%
“…By following one previously published methodology for the preparation of ampicillin-based OSILs [ 5 ], Ferraz & Branco and co-workers [ 3 ] reported the preparation of amoxicillin and penicillin antibiotics as OSILs bearing hydrolyzed β-lactam moieties (respectively seco -AMX- and seco -Pen-OSILs). Despite this shortcoming, on one hand, two of the hydrolyzed seco -Pen-OSILs showed up to a 100-fold increase in antimicrobial activity in vitro against sensitive S. aureus ([C 2 OHMIM][ seco -Pen]) and E. coli ([TEA][ seco -Pen]) strains compared to parent non-hydrolyzed antibiotics.…”
mentioning
confidence: 99%